2010
DOI: 10.1016/j.ces.2009.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase diffusivity of benzene within mesoporous materials measured by a laser Raman technique

Abstract: The intracrystalline diffusivities of benzene within a series of porous materials in the liquid phase (cyclohexane was used as solvent) were measured by a constant volumetric method using Raman spectroscopy at a temperature range from 323 to 393 K.Silicalite-1, mono-dispersed mesoporous silica spheres (MMSS), Silica Gel, -Al 2 O 3 , and SiO 2 -Al 2 O 3 were used as adsorbents. The intracrystalline diffusivity was calculated by parameter fitting using theoretical equations and the experimental transient change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In the vicinity of the silica surfaces, translation and rotation of benzene molecules are much slower than in the bulk and than those of molecules in the pore center. Despite such surface dynamics, which, in agreement with OKE experiments, are nearly independent of the pore size, the dynamics of vicinal benzene is expected to be affected by the pore size for much smaller nanopores (as suggested from the experimental results obtained by Nakasaka et al for nanopores with a diameter close to the size of benzene). In contrast to the results for benzene in the vicinity with silica surfaces, the dynamics of benzene confined in the pore center depends on the pore size but remains very close to their bulk counterpart.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the vicinity of the silica surfaces, translation and rotation of benzene molecules are much slower than in the bulk and than those of molecules in the pore center. Despite such surface dynamics, which, in agreement with OKE experiments, are nearly independent of the pore size, the dynamics of vicinal benzene is expected to be affected by the pore size for much smaller nanopores (as suggested from the experimental results obtained by Nakasaka et al for nanopores with a diameter close to the size of benzene). In contrast to the results for benzene in the vicinity with silica surfaces, the dynamics of benzene confined in the pore center depends on the pore size but remains very close to their bulk counterpart.…”
Section: Discussionsupporting
confidence: 76%
“…Several experimental studies on the dynamics of benzene confined in silica nanopores have been also reported. Using a laser Raman technique, Nakasaka et al have shown that the self-diffusivity of benzene confined in siliceous porous materials (ranging from zeolites to silica gels) increases with increasing the pore size but remains lower than the bulk self-diffusivity. In the case of porous silica gels, Yi and Jonas further showed that the orientational dynamics becomes slower with decreasing the pore size as the reorientational relaxation time scales as 1/ R (where R is the pore radius).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of molecules diffusing in the configurational regime is, therefore, comparable to that of surface diffusion of adsorbed molecules on a surface. 43 Values of configurational diffusion can be significantly smaller compared to free diffusion, 44 hence it is possible in the slow diffusive region, n-octane diffuses in such a regime. Large decreases in diffusivities, similar to these observed in this work for the slow diffusive component, with respect to the unrestricted free self-diffusivity, have been reported for very similar molecules diffusing over the surface of catalyst pores, 45 which is also a good indication of configurational diffusion, for the reasons previously highlighted.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%